Medicinal plants use for respiratory infections in the Post-COVID-19 era: Symptomatic overlap and disease-specific preferences - Ahmed-Gaid, Kelthoum; Hanoun, Saida; Sekkoum, Khaled; Ahmed-Gaid, Hadjer; Chenna, Houssem; Ahmed-Gaid, Nour El Yakine (Ethnobotany Research and Applications, 2025)
Background: In the aftermath of the COVID-19 pandemic, difficulties in self-diagnosing between influenza, the common cold, and COVID-19—from mild to severe cases—have led to potential overlap in the use of medicinal plants. This study investigates whether medicinal plants are employed as symptomatic treatments or in a disease-specific manner. Methods: An ethnobotanical survey was conducted between February 2024 and January 2025 with 72 informants from two Algerian communities, including herbalists, traditional healers, and plant users. The Jaccard Similarity Index (JSI) was used to assess overlap in plant usage, the Fidelity Level (FL) to evaluate disease-specific plant preferences, and the chi-square test to determine associations between plant selection and respiratory diseases. Results: 30 medicinal plant species from 17 botanical families were identified. The Family Importance Value (FIV) highlighted Myrtaceae as the most cited family (FIV = 0.778). JSI revealed a substantial overlap (66.67%) in the use of plants for COVID-19 and for influenza/cold treatment. FL analysis showed that Syzygium aromaticum L. (FL = 90.90%) was highly specific to COVID-19, while Ammi visnaga Lam. (FL = 96%) was predominantly used for flu and colds. The chi-square test (χ² = 41.07, p < 0.05) indicated a statistically significant association between plant use and disease type, confirming that plant selection was not random. Conclusions: These findings provide new insights into post-pandemic trends in medicinal plant use and highlight the continued relevance of traditional knowledge in differentiating plant applications for various respiratory ailments, despite symptom overlap. Keywords: Medicinal plants, COVID-19, influenza, cold, overlap, survey